2014
DOI: 10.1021/jp4120145
|View full text |Cite
|
Sign up to set email alerts
|

Probing Tertiary Structure of Proteins Using Single Trp Mutations with Circular Dichroism at Low Temperature

Abstract: Trp is the most spectroscopically informative aromatic amino acid of proteins. However, the near-UV CD spectrum of Trp is complicated because the intensity and sign of 1La and 1Lb bands vary independently. To resolve vibronic structure and gain site-specific information from complex spectra, deconvolution was combined with cooling and site-directed tryptophan substitution. Low temperature near-UV CD was used to probe the local tertiary structure of a loop and α-helix in tear lipocalin. Upon cooling, the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
(210 reference statements)
2
16
0
1
Order By: Relevance
“…But multiple rotamer populations produce the same phenomena [37]. Because our prior work shows that the rotamer assignments correlate with fluorescent lifetimes in restricted sites it follows that high heterogeneity values are mainly derived from the rotamer mechanism [20, 21, 58]. Contributions from differences in solvent relaxation for various conformational isomers of Trp would be consonant with our results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…But multiple rotamer populations produce the same phenomena [37]. Because our prior work shows that the rotamer assignments correlate with fluorescent lifetimes in restricted sites it follows that high heterogeneity values are mainly derived from the rotamer mechanism [20, 21, 58]. Contributions from differences in solvent relaxation for various conformational isomers of Trp would be consonant with our results.…”
Section: Discussionsupporting
confidence: 85%
“…Trp124, positioned just beyond the N-terminal portion of the α-helix, demonstrates a high rotamer heterogeneity value in concordance with data from low-temperature site-directed CD of TL [58]. Marked enhancement of the 1 L b CD band at low temperature for Trp124 was consistent with a high degree of rotamer population rearrangement, i.e.…”
Section: Discussionsupporting
confidence: 81%
“…As near UV-CD spectra of proteins reflect their tertiary structure through the distinct spatial arrangements of aromatic amino acids, 44,45 potential differences in the tertiary structures and PLP-binding sites among wild-type hALAS2 and XLPP variants were evaluated using CD spectroscopy in the near-UV (310-260 nm) and visible (310-500 nm) regions (Figure 8A). A decreased ellipticity in the near-UV signal associated with the delAT variant indicated that the truncation introduced with the delAT mutation affects the integrity of the tertiary structure of hALAS2 (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…W28 is known to have energetically favored rotamers that promote a holo-conformation at low temperature. 16 The selection of energetically favorable conformations of Trp at low temperature enhances the exciton signal and permit establishing the proximity of these residues within the loop. The enhancement of the amplitude of the couplet for W28W33 is as much as five fold (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work with the near UV CD showed that low temperature altered the distribution of side chain rotamers to populate the lower energy conformation states. 5, 16 It follows that reducing flexible conformations at low temperature should enhance the bisignate exciton coupling signal by increasing the populations of energetically favored conformations in Trp-Trp interactions.…”
Section: Introductionmentioning
confidence: 99%